A Series of Imidazo[1, 2‐f]phenanthridine‐Based Sky‐Blue TADF Emitters Realizing EQE of over 20%. Issue 5 (2nd January 2019) - Ohsawa, Tatsuya; Sasabe, Hisahiro; Watanabe, Taiki; Nakao, Kohei; Komatsu, Ryutaro; Hayashi, Yuya; Hayasaka, Yuya; Kido, Junji
Abstract: Although imidazole derivatives are promising as blue fluorescent emitters in organic light‐emitting devices (OLEDs), the corresponding blue thermally activated delayed fluorescence (TADF) emitter is rarely explored. In this study, a series of imidazo[1, 2‐f]phenanthridine‐based TADF materials in the blue to sky‐blue region is developed. The resultant benzimidazole (BIP)‐based TADF materials, with π‐expanded acceptor and electron‐donor phenoxazine (PXZ), namely PXZ‐BIP, shows a high maximum external quantum efficiency (ηext, max ) of 21% with CIE coordinates of (0.21, 0.37). These results have clearly demonstrated that PXZ‐BIP exhibits the highest ηext, max among imidazole‐based fluorescent sky‐blue OLEDs. The corresponding imidazophenanthridine derivative, with a less π‐expanded acceptor, shows inferior OLED performances, with a ηext, max of 5.9% and CIE of (0.19, 0.30). This study provides a critical molecular design to realize high‐efficiency TADF materials based on imidazole derivatives. Abstract : A fused imidazole‐based blue thermally activated delayed fluorescence emitter is successfully developed. In this study, π‐expanded benzimidazole derivatives are used as an electron‐acceptor unit, and phenoxazine as an electron‐donor unit, realizing a photoluminescent quantum efficiency of 80%. A blue device exhibits a high external quantum efficiency over 20%.